INNOVATION AND CHANGES IN THE DIDACTIC SPACE: Received: 03rd June 2021; Revised: 22nd August 2021, 11th November 2021, 24th February 2022; Accepted: 04th March 2022 - Martinazzo, Francesco (MATTER: International Journal of Science and Technology, 2022)
In Italy, the theme of the school, and more generally of education in the broadest sense, already in turmoil before the epidemic, seems to be exploding today in all its urgency, both because of the instances - above all pedagogical - of transformation brought by the pandemic itself (which from this point of view has acted as a catalyst), and because of the uncertain consequences of a building heritage that now largely needs to be restored, because it is architecturally and technologically inadequate. This has led to the structuring of a literature review that takes into account two main time spans: on the one hand, that of the 1960s-1970s (often called "the golden age of school"), investigated through the international architectural journals of that period, where the typology-technology problem emerges strongly; on the other hand, the selection (through Scopus, WoS, etc.) of current or recent studies and pedagogical experiences related to new technologies. The criterion for the choice of case studies is therefore based on their propulsive potential in relation to today's transformation needs, seeking to consider the school as an organism and not merely as a set of functional parts (as much current literature does).